Quinine induced disseminated intravascular coagulopathy - Nadeem, Muhammad Kashif (Australasian Medical Journal, 2011)
There are only a handful of case reports of Disseminated Intravascular Coagulopathy (DIC) as a result of quinine use however it is important to recognise this early especially when quinine has not been prescribed for managing malaria. Off licence use of any medicine may result in serious complications, quinine induced DIC is one of them.